Identifying the muscle contraction activity at athletes using brain mapping - Enescu Bieru, D.; Rusu, M. R.; Calina, M. L.; Marin, M. I.; Korkmaz, N. C.; Rusu, L. (BRAIN. Broad Research in Artificial Intelligence and Neuroscience, 2021)
Background: Understanding the brain function and how it coordinate the motor activity, means to have a map of brain using a lot of modern technologies which can give us information about the role and functions of different brain areas.